2005
DOI: 10.1081/jdi-200065259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sevelamer on Dyslipidemia and Chronic Inflammation in Maintenance Hemodialysis Patients

Abstract: Hs-CRP levels were reduced by sevelamer administration, as well as non-HDL-C, P, and the Ca x P product. Sevelamer may have an anti-inflammatory effect, in addition to lowering phosphate and lipid levels in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Ferramosca et al (22) showed that sevelamer treatment resulted in significant reductions of serum phosphorus and CRP levels. Likewise, Yamada et al (23) observed a significant decrease of CRP during sevelamer therapy, which was correlated with the change of phosphorus. More recently, a subanalysis from the Nutritional and Inflammatory Evaluation of Dialysis Patients Study showed that patients receiving sevelamer were more likely to have a lower CRP concentration when compared with patients treated with calcium-based phosphate binders (24).…”
Section: Discussionmentioning
confidence: 99%
“…Ferramosca et al (22) showed that sevelamer treatment resulted in significant reductions of serum phosphorus and CRP levels. Likewise, Yamada et al (23) observed a significant decrease of CRP during sevelamer therapy, which was correlated with the change of phosphorus. More recently, a subanalysis from the Nutritional and Inflammatory Evaluation of Dialysis Patients Study showed that patients receiving sevelamer were more likely to have a lower CRP concentration when compared with patients treated with calcium-based phosphate binders (24).…”
Section: Discussionmentioning
confidence: 99%
“…The kinetics of the HDL changes could not be characterized because lipid panels were drawn only at the start and completion of the treatment arms. Of note, most patients in our study were concomitantly treated with sevelamer, which lowers LDL via bile acid binding (27,28). This may obscure further lipid lowering by niacinamide.…”
Section: Discussionmentioning
confidence: 99%
“…5 The direct association of hyperphosphatemia with CRP, as derived from our data, might also serve to duplicate the known cardiovascular disease paradigm linking blood cholesterol levels, dietary intake, and cardiovascular risk with respect to blood phosphate. 9,10 In conclusion, the reduction of serum PO 4 , induced by the chitosan chewing gum, in sevelamer-resistant hemodialysis patients and its relationship with hsCRP reduction, shown in the present study, joined with the demonstration "in vitro" that increased PO 4 concentration impairs endothelial integrity via induction of oxidative stress, 4 and with the evidence that sevelamer reduces both hsCRP and serum phosphate, 5 provide further evidence to support a direct proinflammatory role of hyperphosphatemia. All together these results strengthen the role of serum phosphate as "non-traditional" risk factor for cardiovascular disease, which has been shown even in the normal population.…”
Section: Discussionmentioning
confidence: 99%